Model-Based Fault Detection of a Battery System in a Hybrid Electric Vehicle (Conference) - Gadsden S; Habibi SR (My University, 2011)
Recently, a new type of interacting multiple model (IMM) method was introduced based on the relatively new smooth variable structure filter (SVSF), and is referred to as the IMM-SVSF. The SVSF is a type of sliding mode estimator that is formulated in a predictor-corrector fashion. This strategy keeps the estimated state bounded within a region of the true state trajectory, thus creating a stable and robust estimation process. The IMM method may be utilized for fault detection and diagnosis, and is classified as a model-based method. In this paper, for the purposes of fault detection, the IMM-SVSF is applied through simulation on a simple battery system which is modeled from a hybrid electric vehicle.